2019
DOI: 10.1007/s11664-019-07119-4
|View full text |Cite
|
Sign up to set email alerts
|

Anatase TiO2 Nanotubes-Aggregated Porous Microspheres for Ti Foil-Based Quasi-Solid State Dye-Sensitized Solar Cells with Improved Photovoltaic Performance

Abstract: Fibrous anatase TiO 2 nanotubes-aggregated porous microspheres (AMS) with high specific surface area (160 m 2 g À1) were fabricated through an alkali solution-assisted hydrothermal process followed by an acid post-treatment and a calcination by using commercial TiO 2 nanopowder (P25) as raw material. The resultant AMS microspheres with an average diameter of $ 5 lm have three-dimensional network-like porous structures formed by accumulation and winding of fibrous TiO 2 nanotubes with diameter < 10 nm. When use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…There are many methods to prepare TNTs, such as the anodic oxidation method, 23‐30 the hydro/solvothermal synthesis method, 31‐37 and the template method 7,11‐15 . In the following, the preparation methods of TNTs for DSSCs are explained in more detail.…”
Section: Preparation Methods Of Tnts For Dsscmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many methods to prepare TNTs, such as the anodic oxidation method, 23‐30 the hydro/solvothermal synthesis method, 31‐37 and the template method 7,11‐15 . In the following, the preparation methods of TNTs for DSSCs are explained in more detail.…”
Section: Preparation Methods Of Tnts For Dsscmentioning
confidence: 99%
“…The hydrothermal method is an effective and cost‐effective way to prepare TNTs, 31‐37 and there are 3903 publications on the topic in the Web of Science Core Collection (keywords: TiO 2 nanotubes, hydrothermal, solvothermal, time span:1945‐2020).…”
Section: Preparation Methods Of Tnts For Dsscmentioning
confidence: 99%
“…hindering the long-term stability of DSSCs. [113,114] Recently, a study found DSSCs with solid-state electrolytes with good longterm stability, although, due to the low electrolyte/electrode interface and low conductivity, these solar cells were found to have a decreased PCE. [115] The production cost of DSSCs was less compared to silicon-based and other second-generation solar cells.…”
Section: Large-scale Applications Of Dsscsmentioning
confidence: 99%
“…The corrosion of Pt CEs by redox electrolyte bleaching, leakage of electrolyte (via a decrease in the capability of Bynel® and Surlyn® seals with use), and the detachment of dye molecules from the surface of the working electrode may be considered essential factors hindering the long-term stability of DSSCs. [113,114] Recently, a study found DSSCs with solid-state electrolytes with good long-term stability, although, due to the low electrolyte/ electrode interface and low conductivity, these solar cells were found to have a decreased PCE. [115] The production cost of DSSCs was less compared to silicon-based and other second-generation solar cells.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…Because of their low specific weight, high flexibility, superior tunability, high absorption coefficient, lower cost and high transparency, organic material-based solar cells have remarkable performance. 71 Modifications of the TiO 2 -based photoelectrode used in DSSCs have also been carried out with aggregated microspheres, 72 nanosheet spheres, 73 reduced graphene oxide composites, 74 and quasi-cubic fluorine. 75 Quantum dot sensitized solar cells (QDSSCs) have also gained popularity in recent years.…”
Section: Solar Cellsmentioning
confidence: 99%